FINDINGS AND RESULTS REGARDING THE APPLICATION OF INFORMATION TECHNOLOGY IN ROMANIAN PRE-UNIVERSITY EDUCATION - Alina Petruţa Ţurcanu (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
Our society is constantly changing, but the same thing is happening with technical innovations. Technology not only influences a part of our lives, but manifests itself in all its fields. The form of communications, the pace of life, the work and even the environment have undergone, thanks to this innovation, essential changes. Today there is no talk in vain of the so-called "information society", but this is considered a community whose good - information - has continuously developed. Nowadays the use of information technology brings important changes in the way we learn. Learning must go beyond the classroom and encompass complex disciplines and technologies. Therefore, in today's education it goes from training to learning, where the act of learning is placed before teaching and the student is at the center of the educational process. For specialists in physical education and sport, this trend is also reflected by the need to improve their educational process. A modern alternative is the use of information technology designed to increase the effectiveness of the teaching process.